Research trends and hotspots in BK polyomavirus infection in kidney transplantation - Yanhua Li; Yazhe Duan; Jiazhao Fu; Xiaoying Lu; Wenyu Zhao (Medicine, 2026)
Background: Kidney transplantation has consistently faced challenges due to BK polyomavirus (BKPyV) infection. We aimed to conduct a comprehensive bibliometric analysis to identify research trends and hotspots related to BKPyV infection in kidney transplantation. Methods: Publications concerning BKPyV infection in kidney transplantation were retrieved from the Web of Science Core Collection spanning 1976 to 2024. We conducted bibliometric and visual analyses using VOSviewer, CiteSpace, and the R package bibliometrix. Results: By June 12, 2024, a total of 1809 studies on this topic were included. The overall trend showed an increase in the number of publications, albeit with fluctuations. The United States (n = 474) and the University of Basel (n = 208) were the leading contributors by country and institution, respectively. The journals Transplantation and American Journal of Transplantation ranked first in h-index and impact factor. Notably, Professor H. H. Hirsch was the most prolific author, with 79 publications. Keyword analysis delineated 4 distinct clusters encompassing diagnostic modalities, clinical management strategies, and molecular pathogenic mechanisms. Keyword burst analysis revealed significant periods of intensified research focused on topics such as “histological evolution” and “tacrolimus.” Conclusion: This study provides a bibliometric overview of BKPyV infection research in kidney transplantation. It maps publication output, influential contributors, and evolving research themes. Keyword analyses indicate sustained attention to BKPyV–associated nephropathy, immunosuppression-related management, and emerging interest in histology-related topics, which may help inform future research directions.